Pantothenic Acid, Vitamin C, and Biotin Play Important Roles in the Growth of Lactobacillus helveticus - Yao, Chunxiao; Chou, Jiandong; Wang, Tao; Zhao, Hongfei; Zhang, Bolin (Frontiers in Microbiology, 2018)
Lactobacillus helveticus is an important lactic acid bacterium. The strains used in this study have proven probiotic function, and the potential to produce functional dairy products and bioactive peptides. To explore the effects of vitamins on the growth of Lactobacillus helveticus, a chemically defined medium (CDM) was designed and nine vitamins were tested. Pantothenic acid (Vb5), vitamin C (Vc) and biotin were necessary for the growth of L. helveticus CICC 22171. These three vitamins had an important effect on the glucose metabolism and energy metabolism of strain CICC 22171. Through transcriptomic analysis, we found that three vitamins were related to the synthesis of fatty acids and participate in the energy supply of the cells. Additionally, Vb5 was involved in the metabolism of bacterial proteins and lipids and was related to the activity of various enzymes. The results indicated that Vc was involved in protein metabolism, and biotin affected the intracellular transport mechanism of bacteria. The ability of vitamins to promote the growth of the strain was verified in skim milk medium. The results indicated that vitamin C, biotin and Vb5 could promote the proliferation of L. helveticus but had no significant effect on L. bulgaricus.